1992
DOI: 10.1177/004051759206201107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fabric Deformation in a Roll-Making Operation Part III: Effect of Viscoelasticity

Abstract: The relationship between various parameters of roll making, fabric properties, and the resultant stresses developed within a fabric roll has been discussed in Pans I and I1 of this scries. A discrete continuum modcl was used to describe fabric deformation during roll making. In the present model, the fabric is assumed to be in plane stress state and the effect in the filling direction is entirely neglected. The fabric is considered as anisotropic in warp and thickness directions. The effect of fabric viscoclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…With different combinations of these basic elements we can obtain a number of variations of the basic models such as linear and nonlinear models. The linear models represent the linear relation between the stress and the strain by loading, whereas the nonlinear models show nonlinear or disproportionate relationships [9,10].…”
Section: Stress Relaxation In Woven Fabricmentioning
confidence: 99%
“…With different combinations of these basic elements we can obtain a number of variations of the basic models such as linear and nonlinear models. The linear models represent the linear relation between the stress and the strain by loading, whereas the nonlinear models show nonlinear or disproportionate relationships [9,10].…”
Section: Stress Relaxation In Woven Fabricmentioning
confidence: 99%
“…This can be seen after manually unwinding the first layer of the fabric roll, as there is no change of length of the cut layer after particular relaxation time (Šajn et al , 2003). On the contrary, the stresses in the radial direction from the outside to the inner part of the roll increase (Ghosh et al , 1992). The behaviour of the fabric in the roll as a viscoelastic material is described using the mechanical models, which consist of the basic model of the spring and the dashpot.…”
Section: Elastic Properties Of the Fabrics Containing Elastane Yarnsmentioning
confidence: 99%
“…Batra et al 6 investigated the state of stress in a warp beam through isotropic and anisotropic continuum models, which could be estimated by the anisotropy parameters, such as the wind-thickness, slip-factor, and Poisson's ratio of the material. Ghosh et al [7][8][9][10] identified a discrete continuum model for simulating fabric deformation in the static case. The torque and dynamic factor were applied to the equation of motion of the wound package in the dynamic case.…”
mentioning
confidence: 99%
“…Ghosh et al. 710 identified a discrete continuum model for simulating fabric deformation in the static case. The torque and dynamic factor were applied to the equation of motion of the wound package in the dynamic case.…”
mentioning
confidence: 99%